2020
DOI: 10.3389/fpsyt.2020.585813
|View full text |Cite
|
Sign up to set email alerts
|

A Polish and German Population Study of Quality of Life, Well-Being, and Life Satisfaction in Older Adults During the COVID-19 Pandemic

Abstract: Introduction: Psychological studies undertaken during the COVID-19 pandemic rarely include people in their 60s or older. In our study, we studied the predictors of quality of life, well-being, and life satisfaction (including risky behavior, trait anxiety, feeling of threat, sleep quality, and optimism) during the pandemic in older people from Germany and Poland and compared them to three different age groups. Methods: A total of 494 adults in four groups−60+ ( N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
136
4
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(160 citation statements)
references
References 66 publications
10
136
4
10
Order By: Relevance
“…In relation to age, this study found an inverse association between negative affect and age, indicating that the older the age, the lower the negative affect scores. Along the same lines, other studies found older people had better well-being scores than younger people (e.g., Bidzan-Bluma et al, 2020 ). However, in this study, age did not have significant relationships with positive affect and was not associated with facing COVID-19.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In relation to age, this study found an inverse association between negative affect and age, indicating that the older the age, the lower the negative affect scores. Along the same lines, other studies found older people had better well-being scores than younger people (e.g., Bidzan-Bluma et al, 2020 ). However, in this study, age did not have significant relationships with positive affect and was not associated with facing COVID-19.…”
Section: Discussionmentioning
confidence: 64%
“…In this way, a study found older people rated their quality of life, life satisfaction, and well-being during the pandemic higher than young people, and experienced lower levels of anxiety traits and coronavirus fears than the younger age groups. They experienced greater risk tolerance, sleep quality, and optimism, and had less difficulty relaxing than middle-aged respondents (Bidzan-Bluma et al, 2020 ). Another research study has shown that age was significantly and negatively associated with initial negative affect, but age did not influence the shape or rate of change over time.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest PSS scores were observed in older, less educated respondents, in those who resided with only one other person, and in people who continued with their jobs on-site without shifting to remote work. Age seems to be a general protective factor for stress during pandemic (Bidzan-Bluma et al, 2020;Ruiz et al, 2021), as may be the lack of education in a new situation that requires analytical and interpretational skills to assess potential threats, although dominating evidence is to the contrary (Heanoy et al, 2021). Keeping one's job intact while maintaining social contacts at work is also suggested to be protective against stress (Heanoy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, this group could be particularly affected by the COVID-19 pandemic, potentially experiencing lockdown and its consequences on mental and physical health for a longer time and to a greater degree than others [ 15 , 16 ]. On the other hand, there is emerging evidence from studies of European populations that compared with young and middle-aged adults, older people may be more resilient to some of the negative effects of lockdown: potentially experiencing fewer sleep problems [ 4 ] and mental health consequences [ 17 ] than their younger counterparts. However, the number of studies focusing on the experiences of older people is still limited and very few examine the broad range of potential psychosocial and behavioural consequences of lockdown for this population.…”
Section: Introductionmentioning
confidence: 99%